2015
DOI: 10.5455/msm.2014.27.4-9
|View full text |Cite
|
Sign up to set email alerts
|

Being Immigrant in their Own Country: Experiences of Bosnians Immigrants in Contact with Health Care System in Bosnia and Herzegovina

Abstract: Background:Bosnia and Herzegovina became an independent state (6th April 1992) after referendum for the independence of Bosnia and Herzegovina which was held on 29 February and 1 March 1992. On the referendum voted total 2,073,568 voters (63.6% turnout) and 99.7% were in favor of independence, and 0.3% against. According to the provisions of the peace agreement, particularly in Annex IV of the Constitution of Bosnia and Herzegovina, the country continues to exist as an independent state. Like all others instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that different factors, including social, cultural, ethnicity and educational issues, as well as language barriers, race, gender and religious concerns, may influence a decision against organ donation (5-7). Some of these differences may be explained by different infrastructure, law or consent systems, or the mistrust and corruption in the health-care system, particularly in countries with low deceased donation rates (5, 7, 8). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that different factors, including social, cultural, ethnicity and educational issues, as well as language barriers, race, gender and religious concerns, may influence a decision against organ donation (5-7). Some of these differences may be explained by different infrastructure, law or consent systems, or the mistrust and corruption in the health-care system, particularly in countries with low deceased donation rates (5, 7, 8). …”
Section: Introductionmentioning
confidence: 99%
“…This diversity, which could be considered as a combination of culture and differences in healthcare systems and practical routines between home countries and resettlement countries, influences healthcare services for immigrant patients. Adaption of the healthcare system to the multicultural society is needed, to provide healthcare to all our patients on the same level ( 13 ). In order to provide healthcare services to immigrants, health care professionals need a better and deeper understanding of immigrants’ needs, in view of the immigrants’ cultural background and simple healthcare routines ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to barriers to health care access and efficiency, patients with a migrant background, have a higher prevalence of some chronic diseases than the majority population ( 11 ). Knowledge about attitudes towards health care in different cultures and adapting health care services to multicultural issues is essential to providing equal health care to all inhabitants in multicultural societies ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, immigrants may also face different challenges in their host countries, such as language differences, homesickness for relatives still living in their countries of origin, unfamiliarity with the sociocultural system, unemployment, educational difficulties, and social exclusion, which may affect their view of their GPs’ attitudes (13 - 15) . This is why GPs must be aware of all these obstacles and difficulties that immigrants face and should try to remedy them (38 , 53) .…”
Section: Discussionmentioning
confidence: 99%